The association between quality and quantity of carbohydrate with sleep, mood, anxiety, depression and stress among elderly - Batoul Ghosn; Hanieh Abbasi; Maryam Karim Dehnavi; Parisa Nezhad Hajian; Leila Azadbakht (BMC Geriatrics)
Abstract Background While previous studies have explored the relationship between carbohydrate intake, sleep quality, and mental health, further research is needed to better understand these associations. Our study is specifically examining carbohydrate quality and quantity in relation to sleep, mood, anxiety, stress, and depression to provide deeper insights into these complex interactions. Notably, there is a lack of previous studies focusing on these associations in the elderly population, highlighting the importance of our research. Objectives This study aimed to investigate the association between the quality and quantity of carbohydrate with sleep quality and mental health outcomes, including mood, anxiety, stress, and depression. Methods This cross-sectional study involved 398 Iranian elderly individuals aged 65–85 years, recruited from healthcare centers of Tehran University of Medical Sciences, Iran using simple random sampling. Dietary intake was assessed using a validated 168-item Food Frequency Questionnaire (FFQ). Psychological health was evaluated using the Depression, Anxiety, and Stress Scale (DASS-21). Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI). Mood was assessed using the Profile of Mood States (POMS) questionnaire. Statistical analysis included logistic regression to examine associations between carbohydrate quality and quantity and sleep, mood, anxiety, stress, and depression. Results After adjusting for confounders, higher carbohydrate quantity was associated with increased odds of depression, with marginally significant higher adjusted odds ratios observed in the highest tertile (T3) compared to the lowest tertile (T1) (OR: 3.930, 95% CI: 1.2–12.867, P-trend = 0.04).Also, higher carbohydrate quality, assessed by fiber content, was associated with reduced odds of anxiety, and stress. (OR: 0.117, 95% CI: 0.075–0.419, P-trend < 0.001, OR: 0.307, 95% CI: 0.129–0.733, P-trend = 0.014) respectively. The glycemic load also showed a significant association with sleep quality (OR: 0.159, 95% CI: 0.054–0.468, P-trend < 0.001). Conclusions Our study demonstrates a strong link between carbohydrate quantity and quality (based on fiber content and glycemic load) with sleep and mental health outcomes. Higher carbohydrate quality intake as assessed by fiber content was associated with lower odds of anxiety and stress. Additionally, high carbohydrate quality intake as assessed by glycemic load was linked to improved sleep quality. These findings highlight the benefits of prioritizing high-quality carbohydrates in the diet for mental and sleep health, especially in the elderly population.